2021
DOI: 10.3390/cells10061293
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression as a Hallmark of Critical COVID-19: Prospective Study

Abstract: The dysregulation of both the innate and adaptive responses to SARS-CoV-2 have an impact on the course of COVID-19, and play a role in the clinical outcome of the disease. Here, we performed a comprehensive analysis of peripheral blood lymphocyte subpopulations in 82 patients with COVID-19, including 31 patients with a critical course of the disease. In COVID-19 patients who required hospitalization we analyzed T cell subsets, including Treg cells, as well as TCRα/β and γ/δ, NK cells, and B cells, during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…A lower number of T cells at COVID-19 onset was reported to be a marker of progression to severe disease [ 54 ]. Lower levels of T helper cells, T suppressor cells, T regulatory cells, and CD16 + CD56 + NK cells were reported in critical COVID-19 patients compared with non-critical COVID-19 patients, with impairments in the function of T and NK cells and very low levels of secreted cytokines [ 55 ]. However, Thieme reported that a robust anti-spike, membrane, and nucleocapsid SARS-CoV-2 protein T cell response was not associated with recovery in critical COVID-19 patients [ 56 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…A lower number of T cells at COVID-19 onset was reported to be a marker of progression to severe disease [ 54 ]. Lower levels of T helper cells, T suppressor cells, T regulatory cells, and CD16 + CD56 + NK cells were reported in critical COVID-19 patients compared with non-critical COVID-19 patients, with impairments in the function of T and NK cells and very low levels of secreted cytokines [ 55 ]. However, Thieme reported that a robust anti-spike, membrane, and nucleocapsid SARS-CoV-2 protein T cell response was not associated with recovery in critical COVID-19 patients [ 56 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…In addition to this, the total T lymphocytes, CD4+, CD8+ T lymphocytes and B lymphocyte counts were found to be significantly decreased in severe and critically ill patients on their admission. These results show that SARS-CoV-2 has a negative effect on T-cell mediated immunity [34].…”
Section: Immunological Aspects In Covid-19 and Hlhmentioning
confidence: 77%
“…Immunological changes are one of the hallmarks of COVID-19 [ 18 ]. A study on COVID-19 patients had revealed that the function of T cells and natural killer (NK) cells is critically altered in severely ill patients [ 18 ].…”
Section: Covid-19 and Immunological Changesmentioning
confidence: 99%
“…Immunological changes are one of the hallmarks of COVID-19 [ 18 ]. A study on COVID-19 patients had revealed that the function of T cells and natural killer (NK) cells is critically altered in severely ill patients [ 18 ]. It is found that the ratio between interleukin-2 (IL-2) and interferon-gamma (IFN- γ ) is one of the sensitive indicators of outcome and disease progression [ 18 ].…”
Section: Covid-19 and Immunological Changesmentioning
confidence: 99%
See 1 more Smart Citation